Coconut Water (Cocos nucifera) as Storage Media for the Avulsed Tooth - Aan Mi'dad Arrizza; Amatul Firdaus Ramadhan (Faculty of Dentistry, Universitas Indonesia, 2012)
Avulsion is a condition of tooth displacement outside the socket due to the trauma. In a case of tooth avulsion case of per-manent teeth, the treatment of choice is replanting the tooth back to the socket. The main concern prior to tooth replanta-tion is to maintain the vitality of periodontal ligament (PDL) cells. The vitality of PDL cells is crucial to form new perio-dontal ligament tissue to support the teeth in order to achieve the success of replantation treatment. Therefore the tooth storage media is needed to maintain the vitality of PDL cells. The aim of the present literature review was to discuss the use of coconut water as an alternative storage medium of the avulsed teeth. Coconut water is biologically pure and steril, rich in amino acid, proteins, vitamins and minerals. The electronic composition of coconut water resembles the intracellu-lar fluid. The ability of coconut water to maintain the vitality of PDL cells is due its nutrient component such as protein, amino acid, vitamin and minerals. Previous study showed the ability of coconut water to maintain the viability of PDL cells was comparable to Hank's balanced salt solution (HBSS), storage media that is recommended by the American As-sociation of Endodontics. In conclusion, coconut water is an effective storage medium for avulsed teeth to maintain the vitality of PDL cells. The advantages of the use of coconut water are economical and easily obtained, and therefore ideal to be recommended as a storage medium for avulsed teeth. DOI: 10.14693/jdi.v17i3.39